Jepharasana : ātmakathā tathā anya lakhāṇono anuvāda - Jefferson, Thomas, 1743-1826 (SAMP early 20th-century Indian books project, 1900)
Biography of Thomas Jefferson, 1743-1826, former president of United States and his letters.